Judith Weingarten, Colin F. Macdonald, Joan Aruz, Lara Fabian and Nisha Kumar (eds) Processions: Studies of Bronze Age Ritual and Ceremony Presented to Robert B. Koehl.: Cult and complexity in ancient Crete and the wider Mediterranean - Wallace, Saro (Journal of Greek Archaeology, 2025)
Robert (Bobby) Koehl, well-known for his interests in ritual artefacts and representations, will be honoured to have a Festschrift incorporating this quality and diversity of scholarship, which has been so excellently edited and includes so many warm and heartfelt acknowledgements of his collegiality, throughout the text as well as in an editors’ Introduction and a separate ‘Tributes’ section. More than many Festschriften, the book is a useful up-to-date resource and pointer, with extensive bibliographies, for students of ancient iconography and ritual – primarily in the Bronze Age Aegean, Koehl’s core interest area.